2017
DOI: 10.21037/jtd.2017.03.107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and characteristics of 25 adult cases of pulmonary sequestration

Abstract: Results: We found 25 cases (18 females, 7 males), which underwent surgery and were histologically proven.There were 22 cases of intralobar PS. 7 cases were asymptomatic, 12 had infectious history (including 3 cases of lung abscess and pleural empyema), 4 presented with hemoptysis, 2 with chest pain. The average age to undergo surgery was 38.24, in the asymptomatic group 34, in symptomatic 39.89. In the latter the symptoms preceded the surgery for 2.45-year. Great majority of sequestrations was located in lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 11 publications
0
25
0
2
Order By: Relevance
“…The patient presented in this report is a 58-year-old male who was diagnosed with an intralobar PS, found incidentally when he presented to the emergency department with acute appendicitis. Intralobar PS is a rare condition that usually presents with recurrent infection [6] and symptoms that include chronic or recurrent cough, fever, hemoptysis, chest pain, pneumonia, chills, and back pain [4 , 5 , [7] , [8] , [9] . Infrequently, patients with intralobar PS may be asymptomatic, in which case intralobar PS is typically diagnosed incidentally during chest CT. Case series reviews have reported the percentage of asymptomatic patients to be between 9.7% [7] and 15% [3] .…”
Section: Discussionmentioning
confidence: 99%
“…The patient presented in this report is a 58-year-old male who was diagnosed with an intralobar PS, found incidentally when he presented to the emergency department with acute appendicitis. Intralobar PS is a rare condition that usually presents with recurrent infection [6] and symptoms that include chronic or recurrent cough, fever, hemoptysis, chest pain, pneumonia, chills, and back pain [4 , 5 , [7] , [8] , [9] . Infrequently, patients with intralobar PS may be asymptomatic, in which case intralobar PS is typically diagnosed incidentally during chest CT. Case series reviews have reported the percentage of asymptomatic patients to be between 9.7% [7] and 15% [3] .…”
Section: Discussionmentioning
confidence: 99%
“…10 Aspergillus fungal organisms have been reported in intralobar sequestrations in the past with 38 reported in the literature. [11][12][13][14][15][16][17][18][19][20][21] Considering that the patient had a history of lung infections, it is possible that the Aspergillus organisms represent a superimposed infection in this case. The fact that fungal organisms have been reported in these prior cases suggests a connection to the tracheobronchial tree and possibly an acquired etiology.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence in an adult population was reported as 0.15-6.4% or less than 0.03% (1). Although symptomatic patients have recurrent pulmonary infection, hemoptysis, and chest pain, 28% of patients are asymptomatic (1). A chest radiograph can show the cystic solid mass and parenchymal infiltration (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…Although symptomatic patients have recurrent pulmonary infection, hemoptysis, and chest pain, 28% of patients are asymptomatic (1). A chest radiograph can show the cystic solid mass and parenchymal infiltration (1,2). In some cases, the pseudo-tumor shadow can be observed with no pathologic sign (2).…”
Section: Discussionmentioning
confidence: 99%